Rheological properties of bituminous binder modified with recycled waste toner. (1st October 2021) - Huang, Jiandong; Li, Xin; Kumar, G. Shiva; Deng, Yihao; Gong, Minghui; Dong, Niya
Abstract: Residual waste toner (WT), which is abundantly generating with modern industry, is a potential green resource that can be used as an asphalt modifier for better engineering performance and cost-saving. This study is conducted to comprehensively evaluate the feasibility of using WT as an asphalt modifier considering various rheological properties of the modified binder. Four different WT modified asphalt are prepared (with WT contents of 3%, 6%, 9%, and 12%). The properties of the modified binder were investigated through a series of rheological tests including the conventional binder specification tests (penetration, softening point, ductility, and flash point), multiple stress creep recovery (MSCR), and Bending Beam Rheometer (BBR) tests. Testing results indicated that the incorporation of WT can improve the rheological properties of the asphalt binders at low and high temperatures regardless of the WT contents. Besides, WT was shown a positive impact on fracture and bonding performances. It is noted that asphalt binders containing up to 12% of WT had a significant improvement on high-temperature, intermediate temperature fracture, low-temperature cracking, and moisture sensitivity properties. In the end, the present research shows the residual WT as a value-added modifier is a promising solution with both environmental and engineering merits.